Between privileges and precariousness: Remaking whiteness in China's teaching English as a second language industry. Issue 1 (18th October 2021) - Lan, Shanshan
Abstract:  This research examines the multiple and contradictory racialization of white identities in China's booming ESL (English as a second language) industry. China represents a new geography of whiteness studies beyond Euro‐America due to the transformation of corporeal whiteness into a minority identity as a result of international migration. This research makes distinctions between white privilege as a form of structural domination in Western societies and white‐skin privilege as a form of embodied racial capital in China, which can be easily transformed into white‐skin vulnerability. It interprets the tension between white‐skin privilege and precariousness as a concurrent and mutually constitutive process that foregrounds the open‐ended nature of white racial formation in China. By focusing on the intersections between global white supremacist ideologies and local Chinese constructions of self/Other relations, this project explores new forms of racialization beyond the Black/white, superiority/inferiority binaries in the Western context. Resumen: Esta investigación examina la racialización múltiple y contradictoria de identidades blancas en la industria en auge del ESL (inglés como segundo idioma) en China. China representa una geografía nueva de estudios de blancura más allá de Euro‐América debido a la transformación de la blancura corpórea en la identidad de una minoría como resultado de una migración internacional. Esta investigación hace distinciones entre el privilegio blanco como una forma de dominación estructural en sociedades occidentales y el privilegio de piel blanca como una forma de capital racial corporeizado en China, el cual puede ser fácilmente transformado en vulnerabilidad de la piel blanca. Interpreta la tensión entre el privilegio de piel blanca y la precariedad como un proceso concurrente y mutuamente constitutivo que destaca la naturaleza abierta de la formación racial blanca en China. Al enfocarse en las intersecciones entre las ideologías supremacistas blancas globales y las construcciones chinas locales de las relaciones sí‐mismo/otro, este proyecto explora nuevas formas de racialización más allá de los binarios negro/blanco, superioridad/inferioridad en el contexto occidental. [ privilegio de piel blanca, precariedad, neoliberalismo racial, profesores de inglés extranjeros, China ].